Persepsi Mahasiswa Akuntansi Atas Perilaku Akuntan Publik Dipengaruhi oleh Pengetahuan, Sensitivitas Etis, Idealisme, dan Religiusitas - Prabandari, Kadek Putri; Eka Damayanthi, I Gst Ayu (E-Jurnal Akuntansi; Vol 29 No 3 (2019), 2019)
The purpose of this study was to determine the effect of knowledge, ethical sensitivity, idealism, and religiosity on the perceptions of accounting students on the ethical behavior of public accountants in students in the Faculty of Economics and Business at Udayana University. The sample used amounted to 60 people with multiple linear regression analysis techniques. The results show that knowledge has a positive and significant effect on the ethical perceptions of Udayana University accounting students for the ethical behavior of public accountants. Ethical sensitivity has a positive and significant effect on ethical perceptions of Udayana University accounting students for ethical behavior of public accountants. Idealism has a positive and significant effect on the ethical perception of Udayana University accounting students for ethical behavior of public accountants. Religiosity has a positive and significant effect on the ethical perception of Udayana University accounting students for ethical behavior of public accountants. Keywords : Knowledge;  Ethical Sensitivity;  Public Accounting; Idealism;  Perception.